Optimization of fermentation factors for polyhydroxybutyrate (PHB) production using Bacillus megaterium pncm 1890 in simulated glucose-xylose hydrolysates from agricultural residues - Dañez, John Cristopher A.; Nayve, Jr., Fidel Rey P.; Alfafara, Catalino G.; Requiso, Princess J.; Ventura, Jey-R S. (2020)
The polyhydroxybutyrate (PHB) production performance of Bacillus megaterium PNCM 1890 in multiple carbon sources was assessed in a model system of simulated glucose-xylose hydrolysates from several agricultural residues (corn stover, sugarcane bagasse, and banana pseudostem). Factors investigated were the type of nitrogen source, carbon-to-nitrogen (C/N) ratio, carbon-to-phosphorus (C/P) ratio, and amount of trace elements in the fermentation medium. Results show that the type of nitrogen source had a significant effect on bacterial growth and PHB production, with urea as the most preferred nitrogen source. In contrast, the type of simulated hydrolysate had no significant effect on the behavior of the bacteria, implying that the microorganism can potentially utilize hydrolysates from various agricultural residues. However, considering conversion efficiency and operating cost, simulated corn stover hydrolysate was selected as the best carbon source. A fermentation time of 28 h was found sufficient to completely utilize both glucose and xylose from the simulated hydrolysate. PHB was also confirmed as a growth-associated product of the bacteria, with observable patterns of catabolite repression and diauxic growth. Optimum conditions that maximize biomass concentration (7.3 g/L), PHB concentration (3.91 g/L), and substrate consumption (98.77% for glucose; 93.76% for xylose) were 14.3 g/g C/N ratio, 21.4 g/g C/P ratio, and 8 mL of trace elements solution (TES) per L of fermentation medium. Nonetheless, PHB was successfully produced using simulated corn stover hydrolysate and urea as carbon and nitrogen sources, respectively. The study provides baseline information on the use of actual hydrolysate, efficient fermentation, and upscaled production of bioplastics from agricultural residues. (Author's abstract)
Includes bibliographical references (pages 155-157)
Keywords: Engineering; Banana pseudostem; Corn stover; Sugarcane bagasse; Polyhydroxybutyrate; Response surface methodology; Simulated hydrolysates